Vascular and cellular response to phytohaemagglutinin in Japanese quail - Singh, S D; Mohanty, G C (The Indian Journal of Animal Sciences, 2012)
Intradermal inoculation of 100Âµg phytohaemagglutinin (PHA) in Japanese quail caused a mild increase in vascular permeability which persisted up to I hr post-inoculation (PI). Histologically, a cellular infiltrate rich in heterophils,monocytes and basophils observed during early hours was soon followed by predominant T-Iymphocytes accumulation around many small blood vessels forming well developed lymphoid aggregates at 24-48 hr PI.